The Effect of Microwave Irradiation on the Laser-generated Ag-TiO2 Compound Nanoparticles - Hamad, Abubaker H. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2025)
The pulsed laser ablation technique in liquid solutions is a promising method for generating nanoscale materials due to its chemically clean and simple synthesis process. This study generates spherical Ag-TiO2 compound nanoparticles (CNPs) through pulsed laser ablation, a picosecond (ps) laser, in deionized water. Then the spherical shapes of the CNPs are changed to rod-like shapes using microwave (MW) irradiation in an ordinary MW (continuous- CW) machine at 700 W for 3.5 min. The effect of MWs on the CNPs is investigated. Before and after MW-irradiation, the samples are characterised using ultraviolet-Vis Spectrometer, transmission electron microscope, and scanning electron microscope machines. The results show that the spherical shape of the nanoparticles was changed to rod-like shapes after MW irradiation. Their nominal dimensions range from 50–70 nm to 150–700 nm in width and length, respectively. Changing the morphology of the nanoparticles is important for various applications.